The Use of Chinese Yang/Qi-Invigorating Tonic Botanical Drugs/Herbal Formulations in Ameliorating Chronic Kidney Disease by Enhancing Mitochondrial Function - Tian, Jiayi; Huang, Yuqi; Wu, Tong; Huang, Hsien-Da; Ko, Kam Ming; Zhu, Bao Ting; Chen, Jihang (Frontiers in Pharmacology, 2021)
Abstract Background: Chronic kidney disease (CKD) is a leading cause of morbidity and mortality. Mitochondrial dysfunction has been implicated as a key factor in the development of CKD. According to traditional Chinese medicine (TCM) theory, many Chinese Yang/Qi-invigorating botanical drugs/herbal formulations have been shown to produce promising outcomes in the clinical management of CKD. Experimental studies have indicated that the health-promoting action of Yang/Qi invigoration in TCM is related to the up-regulation of mitochondrial energy generation and antioxidant status. Objective: This review aims to summarize the beneficial effects of Chinese Yang/Qi-invigorating tonic botanical drugs/herbal formulations on the treatment of CKD and its complications, with particular emphasis on the possible role of mitochondria-associated signaling pathways. Methods: A systematic search of “PubMed”, “China National Knowledge Infrastructure (CNKI)” and “Google Scholar” was carried out to collect all the available articles in English or Chinese related to Chinese Yang/Qi-invigorating tonic botanical drugs/herbal formulations and their effects on mitochondrial function and chronic kidney disease. Results and Discussion: The relationship between the progression of CKD and mitochondrial function has been discussed. The effects of Chinese Yang/Qi-invigorating tonic botanical drugs/herbal formulations and their active ingredients, including phytosterols/triterpenes, flavonoids, and dibenzocyclooctadiene lignans, on CKD and related alterations in mitochondrial signaling pathways are also presented in this review. In the future, exploration of the possible beneficial effects and clinical studies of more Yang- and Qi-invigorating botanical drugs/herbal formulations in the prevention and/or/treatment of CKD and the molecular mechanisms relating to the enhancement of mitochondrial functions warrants further investigation. Conclusion: Given the critical role of mitochondrial function in safeguarding renal functional integrity, the enhancement of mitochondrial energy metabolism and antioxidant status in kidney tissue is likely involved in renal protection. Future studies on the biochemical and chemical basis underlying the effects of Chinese Yang/Qi-invigorating tonic botanical drugs/herbal formulations from a mitochondrial perspective will hopefully provide novel insights into the rational development of new drugs for the prevention and/or treatment of CKD.